Language Assessment Literacy: Cases of Pre-Service English Teachers - Prayogo Hadi Sulistio (IJLECR (International Journal of Language Education and Cultural Review), 2023)
Language assessment literacy is a key area for researchers or anyone with an interest in improving the quality of teaching. A good understanding of the development of assessment instruments is very important in the learning process. The aims of the study are to analyze to what extent of pre-service English teachers are academically and professionally prepared to carry out tasks related to assessing students' language skills and to analyze to what extent and how pre-service English teachers perceive language assessment literacy in their teaching practice. This study uses a qualitative method in which interviews are used to collect data. Interviews were conducted with to 20 pre-service English teachers from the Jenderal Soedirman University, English Education Department. The interview questions were developed to incorporate the eight dimensions of language assessment literacy. The results of the study show that academic experience in terms of attending formal education and professional training is very necessary for pre-service teachers. In addition, it is important for prospective English teachers to understand not only the concept of assessment in the teaching process, but understanding the skills to achieve learning objectives through an assessment process using technology.